IMPLEMENTASI TEKNOLOGI SMART PACKAGING PADA PRODUKSI MENDOAN DI TEMPE MAS ARIS PLIKEN BANYUMAS - Anri Kurniawan; Lestari Hanis Adila; Slamet Sulistiadi; Yuwono Triad Adi; Dwi Sukowati; Luthfi Wahab; Ulinna'mah Lady Itsnia; Kurniawan Ermanto; Hastuti Sintawati Dwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Nahdlatul Ulama Purwokerto, 2026)
Pliken is a center of tempe production located in Kembaran District, Banyumas Regency, Indonesia. This area is well known for producing high-quality tempe and mendoan at affordable prices. The implementation method consisted of four stages: preparation, implementation, mentoring, and evaluation. The implementation activities included socialization, training, and assistance using the Participatory Rural Appraisal (PRA) approach. The implementation of smart packaging helped improve the packaging process of mendoan tempe carried out by local tempe producers in Pliken. Smart packaging increased the selling price of tempe from IDR 4,000 to IDR 7,000 per 500 grams. Post-test results indicated that the producers’ knowledge of smart packaging increased by 70% compared to the pre-test results.